2020
DOI: 10.3390/foods9091297
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Degree of Milling on the Nutraceutical Content in Ecofriendly and Conventional Rice (Oryza sativa L.)

Abstract: We investigated the effects of the type of rice and degree of milling (DOM) on the nutraceutical content and antioxidant activity of rice (Oryza sativa L.). The fatty acid (FA), vitamin E homolog, and phenolic contents in organic (OR), pesticide-free (PFR), and conventional rice (CR) decreased significantly with an increase in the DOM of rice grains, particularly for a DOM of 7 and 9 (p < 0.05). The 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity also decreased with the DOM; particularly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…These results were in line with the findings of another research group that investigated the effect of milling on the vitamin E contents of cereals and gains (Ha et al, 2006;Park et al, 2018). The same study confirmed that this effect also contributed to loss during lipid storage; specifically, this study found a considerable reduction in fatty acids with the increase in milling degree (Kim et al, 2020).…”
Section: Mechanical Processessupporting
confidence: 80%
See 2 more Smart Citations
“…These results were in line with the findings of another research group that investigated the effect of milling on the vitamin E contents of cereals and gains (Ha et al, 2006;Park et al, 2018). The same study confirmed that this effect also contributed to loss during lipid storage; specifically, this study found a considerable reduction in fatty acids with the increase in milling degree (Kim et al, 2020).…”
Section: Mechanical Processessupporting
confidence: 80%
“…In general, milling or pressing succeeds peeling and pearling and must be conducted to produce flour, polished grains, oils, juices, or any other by‐product. This step is also involved in the loss of vitamin E and the modification of the vitamin E profile (Ha et al., 2006; Kim et al., 2020; Park et al., 2018). For example, a very recent study demonstrated how milling degree could dramatically reduce the vitamin E contents and profiles of three different rice bran brands; specifically, increasing the degree of milling to the fifth level caused the loss of 60.5% or more of the vitamin E content of all samples regardless of variety and the complete disappearance of γ‐tocopherols in organic rice bran and pesticide‐free rice bran brands (Kim et al., 2020).…”
Section: Natural and Industrial Factors Influencing The Vitamin E Con...mentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidant enzyme activity in seeds was determined by performing the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free-radical scavenging assay, as described previously ( Kim et al, 2020 ). Briefly, 50 μL of the seed extract was added to 950 μL of 0.1 mM DPPH in methanol.…”
Section: Methodsmentioning
confidence: 99%
“…A recent epidemiological study has indicated that the intake of whole-grain products is associated with a reduced risk of various chronic diseases [ 4 ]. Brown rice, as a whole grain, is rich in high levels of biological activity and potentially beneficial health effects compared to white rice, while also providing more bioactive components with antioxidant activity, such as polyphenols and flavonoids, which have benefits for humans [ 5 , 6 ]. Most current studies on brown rice are investigating the effects of a single type of compound with functional activity and the antioxidative capacity of brown rice through phytochemical analysis.…”
Section: Introductionmentioning
confidence: 99%